Perancangan Sistem Informasi Pengelolaan Data Alumni Di Fakultas Hukum Universitas Sebelas Maret Surakarta - sriwijaya sriwijaya; Nuur Rochman Naafian; Kresno Ario Tri Wibowo (Indonesian Journal of Information Technology and Computing (IMAGING), 2022)
The collaboration of Universitas Sebelas Maret Surakarta (UNS) with alumni has a big impact on the development of UNS. Communication between UNS and alumni must run well. Alumni data collection at the Faculty of Law UNS still uses the manual method. This method has a weakness in the alumni tracking process because alumni data is not up to date. Another problem is that there is no means of publication of activity information, this causes every activity carried out to be ineffective. Based on the description of the problem, the formulation of the problem solved in this study is "How to design an information system for managing alumni data at the Faculty of Law, UNS". The problem limitation in this research is centered on the design of an information system for managing alumni data within the UNS Faculty of Law. Alumni data management information system is designed using PHP Native programming language with MySQL database. The method used to design an alumni data management information system uses the System Development Life Cycle (SDLC) with the Waterfall model. The output of this research is a prototype of a website-based alumni data management information system. With the design of the alumni data management information system, it is hoped that it will make it easier for the Student and Alumni Sub-Section at the Faculty of Law UNS to obtain alumni data.